Educated but Uninterested: Exploring the Attitudes of Educated Youth towards Agriculture in Bangladesh - Md. Jahid Hasan (CV. Literasi Indonesia, 2026)
The primary objective of this study is to analyze the tendency of educated youth in Bangladesh to disengage from agriculture and the underlying factors contributing to it. Data were collected from scientific journals, published research papers, and reports from government and non-government organizations. The study was conducted using a qualitative, survey-based approach with thematic analysis. Data were coded into thematic categories, and interrelationships among themes were examined to develop an integrated interpretation. The study covers the period 2015-2026 within the context of Bangladesh. Primary data were obtained from participants, complemented by secondary data, to evaluate the perceptions of educated youth towards agriculture. Findings indicate that disengagement from agriculture among educated youth is multi-dimensional, influenced by social, cultural, financial, structural, technological, and policy-related factors. The education system is predominantly non-agricultural and oriented toward government and private-sector jobs, making agriculture appear risky, low-status, and physically demanding. Land distribution, technological limitations, financial uncertainty, urban migration, and gender-based social barriers further affect participation. Therefore, integrated policy measures, including curriculum modernization, technology-driven agricultural expansion, financial security, and positive shifts in social perceptions, are essential to re-engage educated youth in agriculture.